2017
DOI: 10.1038/s41533-017-0042-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to good asthma control using different medical adherence scales in Latvian asthma patients: an observational study

Abstract: One of the main challenges in asthma control is adherence to pharmaceutical treatment. The aim of this study was to test the association between adherence to asthma medication, control and medical beliefs, cognitive and emotional perceptions using three different validated questionnaires. Beliefs about asthma medicine, cognitive and emotional factors were determined in a cross-sectional survey of patients attending outpatient pulmonologist practices in Latvia (n = 352). The validated Beliefs about Medicines Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 43 publications
2
34
0
1
Order By: Relevance
“…This finding is in line with the conclusion of a meta-analysis including 26 studies on adherence to medication prescribed to treat numerous diseases (Brandes & Mullan, 2014), in which a weak relation between illness perception and adherence behaviour emerged, while a recent study on persons with asthma found however no associations (Smits, Brigis, Pavare, Maurina, & Barengo, 2017). Note that the illness perception assessments in these studies, as in the present one, were based on scales derived from the Common-Sense Model (CSM), in which perceptions of illness are theorized to explain health behaviour (Cameron & Leventhal, 2003;Leventhal et al, 2003).…”
Section: Perceptions Of Adhd Adherence To Medication and Personalitysupporting
confidence: 78%
See 1 more Smart Citation
“…This finding is in line with the conclusion of a meta-analysis including 26 studies on adherence to medication prescribed to treat numerous diseases (Brandes & Mullan, 2014), in which a weak relation between illness perception and adherence behaviour emerged, while a recent study on persons with asthma found however no associations (Smits, Brigis, Pavare, Maurina, & Barengo, 2017). Note that the illness perception assessments in these studies, as in the present one, were based on scales derived from the Common-Sense Model (CSM), in which perceptions of illness are theorized to explain health behaviour (Cameron & Leventhal, 2003;Leventhal et al, 2003).…”
Section: Perceptions Of Adhd Adherence To Medication and Personalitysupporting
confidence: 78%
“…Note that the illness perception assessments in these studies, as in the present one, were based on scales derived from the Common-Sense Model (CSM), in which perceptions of illness are theorized to explain health behaviour (Cameron & Leventhal, 2003;Leventhal et al, 2003). Hence, the conclusion is that CSM are only weakly linked with adherence to medication, and therefore the CSM framework is only poorly supported by our and others' results (Brandes & Mullan, 2014;Smits et al, 2017). In addition, the B-IPQ seems to be of limited value in adherence assessments in adolescents with ADHD.…”
Section: Perceptions Of Adhd Adherence To Medication and Personalitymentioning
confidence: 68%
“…16 (44%) of the studies reported on patients using preventer asthma medications [33,39,41,44,[50][51][52][54][55][56]62,66,68,[70][71][72], seven (19%) on a combination of preventer and reliever therapies [13,42,45,47,48,67,69]; eight (22%) on different treatments for different groups within the studies (monotherapy and combination therapies) [49,53,[57][58][59]61,63,64]. In five (14%) of the studies, no type of medication was stated [40,43,46,60,65].…”
Section: Prescribed Medicationmentioning
confidence: 99%
“…Twenty-four of the studies (67%) [13,39,41,42,[44][45][46][48][49][50][52][53][54]56,57,60,61,65,[67][68][69][70][71][72] used specifically designed study-specific questions to explore patients' perceptions of treatment including beliefs, behaviours and attitudes toward medications. The validated Beliefs about Medicines Questionnaire (BMQ), which measures patient treatment beliefs, was used in 12 (33%) studies [33,40,43,47,51,55,58,59,[62][63][64]66], whilst five (14%) used the validated Illness Perceptions Questionnaire [33,43,58,59,66] which elicits patient beliefs about their illness.…”
Section: Psychological Componentmentioning
confidence: 99%
See 1 more Smart Citation